2017
DOI: 10.3389/fmicb.2017.01154
|View full text |Cite|
|
Sign up to set email alerts
|

Genome Data Provides High Support for Generic Boundaries in Burkholderia Sensu Lato

Abstract: Although the taxonomy of Burkholderia has been extensively scrutinized, significant uncertainty remains regarding the generic boundaries and composition of this large and heterogeneous taxon. Here we used the amino acid and nucleotide sequences of 106 conserved proteins from 92 species to infer robust maximum likelihood phylogenies with which to investigate the generic structure of Burkholderia sensu lato. These data unambiguously supported five distinct lineages, of which four correspond to Burkholderia sensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 68 publications
6
67
0
8
Order By: Relevance
“…The genus Paraburkholderia was established from a division within the Burkholderia according to phylogenomic evidence [1]. The two genera were subsequently subdivided into four more genera, including Trinickia, Caballeronia, Robbsia and Mycetohabitans [2,3]. Five Paraburkholderia type strains were transferred to the genus Cabellaronia (P. glathei, P. grimmiae, P. humi, P. sordidicola and P. zhejiangensis), three to Trinickia (P. caryophylii, P. soli and P. symbiotica), two to Mycetohabitans (P. endofungorum and P. rhizoxinicia) and one to Robbsia (P. andropogonis) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Paraburkholderia was established from a division within the Burkholderia according to phylogenomic evidence [1]. The two genera were subsequently subdivided into four more genera, including Trinickia, Caballeronia, Robbsia and Mycetohabitans [2,3]. Five Paraburkholderia type strains were transferred to the genus Cabellaronia (P. glathei, P. grimmiae, P. humi, P. sordidicola and P. zhejiangensis), three to Trinickia (P. caryophylii, P. soli and P. symbiotica), two to Mycetohabitans (P. endofungorum and P. rhizoxinicia) and one to Robbsia (P. andropogonis) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This changed with the discovery of nodulating Burkholderia and Cupriavidus strains, both of which belong to the β-proteobacteria ( Chen et al, 2001 ; Moulin et al, 2001 ; Bontemps et al, 2010 ). The number of legume nodulating strains belonging to the environmental clade of the genus Burkholderia , for which the new genus Paraburkholderia has been proposed recently ( Sawana et al, 2014 ; Beukes et al, 2017 ), has increased rapidly over the last years ( Gyaneshwar et al, 2011 ; Howieson et al, 2013 ; Lemaire et al, 2015 ). These strains of the Paraburkholderia clade were shown to nodulate a wide range of legumes, among them several Mimosa species (sub-family Mimosoideae) and Papilionoid legumes from different tribes and from several regions of the world ( Chen et al, 2003 ; Chen et al, 2005a ; Elliott et al, 2007b ; dos Reis et al, 2010 ; Liu et al, 2012 ; Mishra et al, 2012 ; Bournaud et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that bacteria from the genus Paraburkholderia (former Burkholderia) are the main symbionts of Mimosa species in the central region of Brazil (Chen et al 2005a;Elliott et al 2007a;Bontemps et al 2010;Reis Junior et al 2010), French Guiana, Costa Rica, and in areas where such plants were introduced such as Asia and Australia (Chen et al 2005b; Barrett and Parker 2006;Parker et al 2007;Liu et al 2012;Mishra et al 2012;Gehlot et al 2013;Melkonian et al 2014). A division of the genus Burkholderia was recently proposed, involving the creation of a novel genus Paraburkholderia containing the primarily environmental and plantassociated species which broadly corresponds to the BPlant Beneficial and Environmental (PBE)ĉ lade of Suárez-Moreno et al (2012), and which separates them from Burkholderia sensu stricto, which encompasses some environmental strains, but is particularly known for its human clinical and phytopathogenic species (Sawana et al 2014;Beukes et al 2017). All known nodulating Burkholderia species are currently placed in the genus Paraburkholderia, the exception being B. symbiotica which is most likely to be placed in a new genus along with some other members of the BTransition Group I^defined by Estrada-de los Santos et al 2016, such as B. caryophylli, B. soli and B. rhizoxinica.…”
Section: Introductionmentioning
confidence: 99%